2013
DOI: 10.1212/cpj.0b013e3182a78fb1
|View full text |Cite
|
Sign up to set email alerts
|

Expenditures in the elderly with peripheral neuropathy

Abstract: SummaryTo optimize care in the evaluation of peripheral neuropathy, we sought to define which tests drive expenditures and the role of the provider type. We investigated test utilization and expenditures by provider type in those with incident neuropathy in a nationally representative elderly, Medicare population. Multivariable logistic regression was used to determine predictors of MRI and electrodiagnostic utilization. MRIs of the neuroaxis and electrodiagnostic tests accounted for 88% of total expenditures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Importantly, the neurologist’s clinical history and examination and a few simple blood tests provide the clues for identifying the underlying cause of most neuropathies. However, electrodiagnostic tests and MRIs, which account for the vast majority of the expenditures in the evaluation of DSP, 57 rarely lead to changes in etiology and management, and therefore the role of these tests requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the neurologist’s clinical history and examination and a few simple blood tests provide the clues for identifying the underlying cause of most neuropathies. However, electrodiagnostic tests and MRIs, which account for the vast majority of the expenditures in the evaluation of DSP, 57 rarely lead to changes in etiology and management, and therefore the role of these tests requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…24 Not surprisingly, the evaluation of peripheral neuropathy can be quite costly, with most of the cost driven by electrodiagnostic and MRI testing. 57 Given the high aggregate costs associated with this evaluation, determining the value of these diagnostic tests becomes of paramount importance.…”
Section: Introductionmentioning
confidence: 99%
“…While NCS have demonstrated diagnostic value, they are often normal in patients with early or small fiber predominant neuropathy. Electrodiagnostic studies have been identified as one of the largest drivers of health care costs related to neuropathy evaluation(Callaghan et al, 2013). Numbness and sensory complaints are one of the most common symptoms practicing neurologists encounter.…”
Section: Discussionmentioning
confidence: 99%
“…19 In contrast, electrodiagnostic tests and MRI of the brain and/or spine rarely change management of these patients despite being frequently performed and contributing to most of the cost associated with the evaluation of DSP. 32 Electrodiagnostic tests led to a change in management in only 2 of 458 DSP patients seen by community neurologists despite being ordered in 80% of the population. 19 Electrodiagnostic tests clearly have a role in the evaluation of some DSP patients, but the precise subgroup of patients that benefits has not been well defined.…”
Section: Methodsmentioning
confidence: 99%